Simultaneous value-added utilization of photogenerated electrons and holes on Pd/TiO2 - Boxin Liu; Zhuofeng Hu; Yanfang Li; Xin Tan; Jinhua Ye; Tao Yu (Nature Communications)
Abstract The biggest challenge facing the advancement of photocatalytic technology so far is how to achieve the simultaneous and efficient utilization of photogenerated electrons and holes for dual value-added chemicals. Here we show that Pd/TiO2 with electronic metal-support interaction realizes photocatalytic H2O2 evolution coupled with furfural selective oxidation to furoic acid. We demonstrate that the electronic structure of Pd is modulated to form Pdδ+ active sites and upshifted d-band center via electronic metal-support interaction, enhancing O2 adsorption and H2O2 evolution performance, and the photogenerated holes from TiO2 oxidize furfural undergoing the Aldehyde-Water Shift to furoic acid by sequential breaking of O-H and C-H bonds. The optimal Pd/TiO2 achieves H2O2 and furoic acid evolution rates of 3672.31 and 4529.08 μM h−1 with furfural conversion of 92.66% and furoic acid selectivity of 97.82%. Our work provides a promising approach for enhancing synergistic photosynthesis of dual value-added chemicals, thus advancing carbon neutrality goals.